تحليل الفرص الاستثمارية المتاحة في العراق وخيارات التمويل (المجلة العراقية للعلوم الاقتصادية, 2018)
Investment play an important part in activating and advancement of any economy and shed light on the importance of this investment in Iraqi economy . But there are a set of problems , the preclude these local investments which led to ceasing its development although there are several investment opportunities in various sectors on the level of Iraqi Governorates . One of these problems regarding the needed capital to exploit these investment opportunities . As Iraq is need for new financial sources to reconstruct part of what wars and siege had destroyed , and the problem of experts and skills needed to establish the projects ( the opportunities). So the research presented a map for investment opportunities in various sectors for all Iraqi Governorates and their analysis. In the same time the research emphasized that this is a result of the weakness in financy the budget in fields of investment and Banking sectors . And their effectiveness in activating the local investment in Iraq. And the manner of financing these investment opportunities must come from foreign investment which remedy these economic problems in field of financing as well as to overcome unemployment .